1991
DOI: 10.1098/rspb.1991.0137
|View full text |Cite
|
Sign up to set email alerts
|

The development of swimming rhythmicity in post-embryonic Xenopus laevis

Abstract: The post-embryonic development of 'fictive' swimming in immobilized Xenopus laevis tadpoles has been examined during the first day of larval life. In Xenopus embryos (stage 37-38; Nieuwkoop & Faber 1956), the rhythmic ventral root activity underlying swimming occurs as single brief (ca. 7 ms) compound impulses on each cycle. However, by stage 42 (about 24 h after hatching), ventral root discharge consists of bursts lasting around 20 ms per cycle. In addition to increased burst duration in each cycle of larval … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…As previous reports on swimming X. laevis hatchlings reported that the frequency of the head/tail oscillations decreased gradually over the course of a given swimming episode Sillar and Roberts, 1993;Sillar et al, 1991), the difference between the mean frequency of the first two and the last two half-cycles of each episode was calculated ( Fig. 4B; 221 episodes in N=25 animals) and found not to be significantly different from zero (one-sample Wilcoxon signed-rank test, P>0.05).…”
Section: Consistency Of Kinematic Parameters Over Repeated Swimming Ementioning
confidence: 84%
See 2 more Smart Citations
“…As previous reports on swimming X. laevis hatchlings reported that the frequency of the head/tail oscillations decreased gradually over the course of a given swimming episode Sillar and Roberts, 1993;Sillar et al, 1991), the difference between the mean frequency of the first two and the last two half-cycles of each episode was calculated ( Fig. 4B; 221 episodes in N=25 animals) and found not to be significantly different from zero (one-sample Wilcoxon signed-rank test, P>0.05).…”
Section: Consistency Of Kinematic Parameters Over Repeated Swimming Ementioning
confidence: 84%
“…While mostly attached to a substrate between stages 37 and 38 (Boothby and Roberts, 1992; Jamieson and Roberts, 2000), the propensity of Xenopus larvae to spontaneously swim freely increases after the onset of active feeding at stage 45 (Nieuwkoop and Faber, 1956), as confirmed by a developmental study on fictively swimming animals (Currie et al, 2016). At this time, the frequency of the tail undulations is generally high (10-25 Hz; and each swimming bout is characterised by decreasing frequencies over the course of the episode Sillar and Roberts, 1993;Sillar et al, 1991). This contrasts with the observation in the older and thus larger tadpoles studied here, where the swimming frequency remains largely constant throughout a given episode (Fig.…”
Section: Developmental Changes In Locomotor Patternsmentioning
confidence: 93%
See 1 more Smart Citation
“…In this way, inhibition from aINs may also help to synchronize the firing of CPG neurons on the same side and lead indirectly to better alternation between the two sides. aIN inhibition may become more important later in development when Xenopus motoneuron fire multiply on each cycle of swimming (Sillar et al, 1991). In the case of sensory pathway dlc interneurons, aIN inhibition gates the flow of sensory input so that reflex responses are modulated to fit with ongoing swimming activity Roberts, 1988, 1992;Li et al, 2002).…”
Section: Ascending Interneurons Have Two Inhibitory Roles During Swimmentioning
confidence: 99%
“…Xenopus embryos and larvae were prepared for extracellular ventral root recordings in accordance with the UK Animals (Scientific Procedures) Act, 1986, using previously described methods (Sillar et al 1991;Dale, 1995b). Drug access was facilitated by bilateral removal of the rostral myotomes and loosening the dorsal attachment of the remaining myotomes.…”
Section: Extracellular Recordingsmentioning
confidence: 99%